Why does Existential Threat Promote Intergroup Violence? Examining the Role of Retributive Justice and Cost-Benefit Utility Motivations - Hirschberger, Gilad; Pyszczynski, Tom; Ein-Dor, Tsachi (Frontiers in Psychology, 2015)
The current research examined the role of retributive justice and cost-benefit utility motivations in the process through which mortality salience increases support for violent responses to intergroup conflict. Specifically, previous research has shown that mortality salience often encourages political violence, especially when perceptions of retributive justice are activated. The current research examined whether mortality salience directly activates a justice mindset over a cost-benefit utility mindset, and whether this justice mindset is associated with support for political violence. In Study 1 (N=209), mortality salience was manipulated among Israeli participants who then read about a Hamas attack on Israel with either no casualties or many casualties, after which justice and utility motivations for retribution were assessed. Study 2 (N=112), examined whether the link between death primes and support for an Israeli preemptive strike on Iran’s nuclear facilities is mediated by justice or cost-benefit utility considerations. Results of both studies revealed that primes of death increased justice-related motivations, and these motives, rather than utility motives, were associated with support for violence. Findings suggest that existential concerns often fuel violent intergroup conflict because they increase desire for retributive justice, rather than increase belief that violence is an effective strategy. These findings expand our knowledge on the motivations for intergroup violence, and shed experimental light on real-life eruptions of violent conflict indicating that when existential concerns are salient, as they often are during violent conflict, the decision to engage in violence often disregards the utility of violence, and leads to the preference for violent solutions to political problems – even when these solutions make little practical sense.